2017
DOI: 10.1080/10255842.2017.1302434
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady computational fluid dynamics in front crawl swimming

Abstract: The development of codes and power calculations currently allows the simulation of increasingly complex flows, especially in the turbulent regime. Swimming research should benefit from these technological advances to try to better understand the dynamic mechanisms involved in swimming. An unsteady Computational Fluid Dynamics (CFD) study is conducted in crawl, in order to analyse the propulsive forces generated by the hand and forearm. The k-ω SST turbulence model and an overset grid method have been used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Due to the difficulty of quantifying the complex, unsteady flow profile around the whole body during swimming, it is currently not possible to measure both propulsive and resistive forces directly [3]. For this reason, there have been several estimative methods established that allow researchers to assess propulsive and/or resistive forces together with a swimming velocity, such as the MAD system [4], the velocity perturbation method [5], and the assisted towing method [6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty of quantifying the complex, unsteady flow profile around the whole body during swimming, it is currently not possible to measure both propulsive and resistive forces directly [3]. For this reason, there have been several estimative methods established that allow researchers to assess propulsive and/or resistive forces together with a swimming velocity, such as the MAD system [4], the velocity perturbation method [5], and the assisted towing method [6].…”
Section: Introductionmentioning
confidence: 99%
“…η O , overall efficiency; η P, propelling efficiency; η H , hydraulic efficiency; η F , Froude efficiency. during swimming is currently not possible due to a complex unsteady state of the water during swimming (Samson et al, 2017). However, the day-to-day variability of this method to assess D A of the same swimmers was reported to be around 3.0-6.5% (Narita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the important kinematic parameters in the generation of propulsive forces are: the angle of attack of the fluid with respect to the hand, the orientation of the arms with respect to the direction of advancement, the velocity and acceleration of the hand and forearm. Optimal angles of attack range from 45 to 70 (Samson et al 2017). This corresponds to the angles we measured on expert swimmers: 62 on average during the insweep phase and 40 during the upsweep phase (Samson et al 2015).…”
Section: Basic Kinematic Parametersmentioning
confidence: 56%
“…At the same time, numerical simulations have been made using a Unsteady Reynolds Averaged Navier Stokes (URANS) method in order to obtain all the data (pressure, force, velocity) but also to follow the spatio-temporal evolution of the vortices over time. (Samson et al 2017(Samson et al , 2018b, Figure 1). These vortices play a key role in the generation of propulsive forces.…”
Section: Methodsmentioning
confidence: 99%